Common pediatric medical procedures. Umbilical catheterization - Kelleher, Kelly J.; American Academy of Pediatrics ([Elk Grove Village, Illinois] : American Academy of Pediatrics, 2014)
A complete review and demonstration of the procedure for umbilical catheter placement, including full demonstrations for arterial and venous umbilical catheterization.
Presenter: Kelly J. Kelleher.
Online resource; title from opening/closing credits (Digitalia Film Library, viewed October 16, 2020)
Keywords: Arterial catheterization; Catheterization; Umbilical cord; Pediatrics; Documentary films; Instructional films; Nonfiction films; Internet videos; Streaming video; Short films